2007
DOI: 10.3201/eid1307.070848
|View full text |Cite
|
Sign up to set email alerts
|

Large Water Management Projects and Schistosomiasis Control, Dongting Lake Region, China

Abstract: Two large water projects will likely extend the range of snail habitats and increase schistosome transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…2), but many have been displaced into growing urban centers such as Chongqing. Estimates for population displacement from the Three Gorges Dam vary widely, but at least 1 million people have already been relocated (Cernea, 2003;Sleigh, 2006;Li et al, 2007). Recently the Chinese government has suggested that perhaps as many as 4 million will ultimately be relocated, which constitutes a quarter of the population living in the reservoir area (Stone, 2008).…”
Section: Social Healthmentioning
confidence: 97%
See 2 more Smart Citations
“…2), but many have been displaced into growing urban centers such as Chongqing. Estimates for population displacement from the Three Gorges Dam vary widely, but at least 1 million people have already been relocated (Cernea, 2003;Sleigh, 2006;Li et al, 2007). Recently the Chinese government has suggested that perhaps as many as 4 million will ultimately be relocated, which constitutes a quarter of the population living in the reservoir area (Stone, 2008).…”
Section: Social Healthmentioning
confidence: 97%
“…With some notable exceptions (e.g., Jobin, 1999;Sleigh et al, 2006;Li et al, 2007), research programs and efforts on the Three Gorges Dam and human health exist in disparate spheres, resulting in a fragmented approach to what is essentially a linked human-environment system. Although reductionist approaches are necessary, there also is a need for integrative science to more appropriately inform policy.…”
Section: Transdisciplinary Approaches To Understanding Ecosystem Chanmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, schistosomiasis infection is transmitted through humans and other mammalian hosts that contact cercariae released by snails when they are exposed to infested water (Li et al 2007). The Dongting Lake region, which is located in the middle and lower reaches of the Yangtze River, is one of the major and typical lake and marshland areas in China where schistosomiasis is endemic (Yu et al 2002;McManus et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis, which is caused by the trematode blood fluke Schistosoma japonicum, is a major public health problem in China Li et al 2007;. At the beginning of the national control programs during the mid-1950s, schistosomiasis was endemic in 12 provinces along the Yangtze River, and millions of Chinese had died or been disabled because of the disease (Li et al 2000).…”
Section: Introductionmentioning
confidence: 99%